Multidetector Computed Tomography in Traumatic and Nontraumatic Aortic Emergencies: Emphasis on Acute Aortic Syndromes. Issue 3 (August 2020) - Sathiadoss, Paul; Haroon, Mohammad; Wongwaisayawan, Sirote; Krishna, Satheesh; Sheikh, Adnan M.
Aortic emergencies comprise of a list of conditions which are uncommon but are potentially fatal. Prognosis is usually determined by emergent diagnosis and treatment and hence radiology plays a key role in patient management. In this article, we aim to review the various causes of aortic emergencies and the relevant imaging findings placing special emphasis on acute aortic syndromes.